potensi POTENSI ISOLAT JAMUR ENDOFIT DARI DAUN TANAMAN KETEPENG CINA (Cassia alata L) DALAM MENGHAMBAT PERTUMBUHAN JAMUR Malassezia furfur - Rifka Sadapu; syam S kumaji; Adnan Malaha (Jurnal Ilmiah dr. Aloei Saboe, 2021)
This study aims to determine the effect of endophytic fungal isolates from the leaves of the Chinese Ketepeng (Cassia alata L) plant on the growth of Malessezia furfur and to determine the significant differences of each treatment of endophytic fungal isolates from the leaves of the Chinese Ketepeng (Cassia alata L) plant on the growth of Malessezia furfur. The method in this study used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments were: JEKA 1 (Chinese Ketepeng Endophytic Fungus 1), JEKA 2 (Chinese Ketepeng Endophytic Fungus 2), Positive Control (Ketoconazole), and Negative Control (Aquadest). The results showed that 2 isolates of endophytic fungi were successfully isolated from the leaves of the Chinese Ketepeng plant. After testing the inhibitory power against the Malassezi furfur fungus, the JEKA 1 isolate obtained an inhibition zone value of 10 mm and the JEKA 2 isolate an inhibitory zone value of 11 mm. The results of the analysis using the Kruskal-Walis test showed that there was an effect of endophytic fungal isolates from the leaves of the Chinese ketepeng plant (Cassia alata L) on the growth of the fungus Malassezia furfur. Then from the results of further tests using Duncan's test, it was found that each treatment, namely the negative control treatment was significantly different from JEKA 1, JEKA 2 and positive control, while there was no significant difference between JEKA 1, JEKA 2 and positive control.